Droit de suite a wyczerpanie prawa - Jakimczuk, Ewa (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The aim of the present study is to clarify the term droit de suite, as defined in the Act on Copyright and Related Rights. The aforementioned set of regulations is intended to serve a noble purpose: to ensure the just distribution of profit in the event of a rise in the value of a work of art. Droit de suite (resale right) is in force through article 19-195 of the Act on Copyright and Related Rights. It is an inalienable right which entitles the creator and his heirs to an additional remuneration (in the form of a percentage of the profit) in the case of professional resale of original copies of an artwork or photograph. The present paper discusses the rules and regulations applicable to droit de suite, as well as related issues, such as: the legal nature of droit de suite, the liability of sellers in the case of non-compliance, the justifiability of the regulations’ existence in view of the authorities’ inability to enforce them, the advantages and disadvantages stemming from the intermediation of copyright collectives in the sale of works of art.